Cannabinoid Derived Product is a Potential Novel Therapeutic for Papillary Thyroid Carcinoma - Carolina Taico Oliva BS; Ibrahim Musa PhD; Fariba Ardalani MS; Joseph Breslin PhD; Nan Yang PhD; Augustine Moscatello MD; Janine Rotsides MD; Raj Tiwari PhD; Jan Geliebter PhD; Xiu-Min Li MD, MS, MPH (Integrative Cancer Therapies, 2025)
Rationale: Papillary thyroid carcinoma (PTC) is the most common thyroid cancer that typically affects women ages 20 to 50, presenting as an asymptomatic neck mass. Treatment with total or partial thyroidectomy shows an excellent prognosis. However, investigation of non-invasive therapeutic options with minimal adverse effects is ongoing. This study seeks to investigate the K1 cell line, which consists of PTC cells obtained from metastatic tumors of well-differentiated PTC. Objective: Our investigation focuses on a cannabinoid-based product (named BRF1-A) and its potential anti-cancer effects through modulation of gene expression. We investigated its effects on gene expression of p53, c-Myc, and BCL-2 in K1 papillary thyroid cancer cells. Methods: BRF1A was co-cultured with K1 cell line (1 × 10 6 cells/ml) and incubated at 37°C under 5% CO 2 for 24 and 48 hours. After the culture time points, the cells were harvested, and cell viability was determined via trypan blue exclusion assay. Using qRT-PCR, we determined the effect on the gene expression of TP53, c-Myc, and BCL-2. Results: Results show that the BRF1A decreased the viability of K1 PTC cells in a dose and time-dependent manner. Within 24 hours, the cannabinoid- containing product increased the gene expression of TP53 and decreased the gene expression of BCL-2 and c-Myc in K1 PTC cells. Conclusion: The results suggest that the cannabinoid-containing product BRF1A interacts as a potential regulator in well-differentiated thyroid cancer with the upregulation of p53 and downregulation of BLC-2 and c-Myc. Further in vitro and in vivo studies are needed to understand the exact mechanism and therapeutic potential of the cannabinoid-containing products in papillary thyroid cancer.